Children Virtual Concert in the Covid-19 Pandemic - Putu Sandra Devindriati Kusuma (Journal of Music Science, Technology, and Industry, 2020)
Purpose: This article aims to see a children virtual concert held by La Prima Course and Bandung Philharmonic. Both of them held an online concert in June 2020, when the world was entering new normal era due to Covid-19 pandemic. Research methods: The method used in writing this article is descriptive-qualitative by observing watching two virtual concert and long-distance interviews through social media. Results and discussion: Children virtual concert have a positive impact for children as activities at home during the Covid-19 pandemic. Other impacts were also felt by the organizers so that the organizers were enthusiastic to routinely hold virtual performances. Implication: Covid-19 pandemic makes virtual performance a cost-effective and attractive choice for organizers, children, and parents who concern about art.